The Influence of Brand Awareness on Purchase Intention Among TikTok Users in Padang: The Mediating Role of Influencer Endorsement and Influencer Credibility - Deo Al Fajri; Whyosi Septrizola (Journal of Management and Administration Provision, 2025)
The development of digital marketing through social media has encouraged many companies and businesses to utilize influencers as part of their brand communication strategy. This research aims to examine the effect of brand awareness on purchase intention with influencer endorsement and influencer credibility as mediating variables. The issue discussed is how brand awareness can shape consumer purchase intention directly or indirectly through influencer endorsement and influencer credibility. This study employs a quantitative research design utilizing a structured survey approach, with a sample of 200 participants selected through purposive sampling. The gathered data were analyzed using SmartPLS software. The results indicate that brand awareness significantly impacts in-fluencer credibility, influencer endorsement, and purchase intention. Additionally, both influencer endorsement and influencer credibility were shown to positively impact purchase intention. Other results indicate that the indirect influence of brand awareness on purchase intention through influencer credibility and influ-encer endorsement is significant, confirming that influencers have a strategic role in building consumer trust and purchase intention. This study concludes that enhancing brand awareness and engaging credible influencers through effective endorsement strategies are essential in fostering consumer purchase intention and guiding their purchasing decisions.